Social Spending in Korea : Can it Foster Sustainable and Inclusive Growth? - Elekdag, Selim (IMF Working Papers; Working Paper ;, 2012)
Going forward, Korea faces two closely related challenges: sustaining economic growth against the backdrop of a rapidly aging population and ameliorating income inequality. This paper argues that a gradual increase in social spending could promote more sustainable and inclusive growth in Korea. In particular, simulation results suggest that social spending which supports labor market reforms can boost longer-term growth. However, despite rapid increases recently-albeit from a low base-there is still a social spending gap relative to Korea's OECD peers. Because of several fiscal challenges in the coming decades, increases in social spending should be incremental, and would be usefully guided by a longer-term fiscal framework.